Синтез СМС-коммуникаций через Internet - Ткаченко, Владимир Антонович; Гричковский, Т. Я. (НТУ "ХПИ", 2014)
В статье рассмотрены проблемы анализа и синтеза веб-приложений по рассылке СМС-сообщений через Интернет и вопросы разработки методов построения СМС-коммуникаций. Обоснован выбор протоколов и СМС-шлюзов. На Ruby on Rails разработаны программный код веб-приложения с Web- и API (RESTful) интерфейсами, библиотека взаимодействия веб-приложения с СМС-шлюзом и графический интерфейс клиентской части веб-приложения.

In the article the problems of analysis and synthesis of web-applications are considered on distribution of SMS messages over the Internet and questions of development of methods of creation of SMS communications are considered. The choice of protocols and SMS of gateways is reasonable. Software code was developed via Ruby on Rails for web applications and for the library of interaction between web application SMS Getaway and the GUI client part of the web application.
Synthesis of SMS communications through Internet
Keywords: СМС-сервисы; СМС-шлюзы; СМС-сообщения; СМС-центры; WEB-интерфейс; API; SMS services; SMS Gateway; SMS messages; SMS centers